Pre-implementation capacity building training on SI-MFS initiative - Mengistu, Dejene Kassahun; Kidane, Yosef Gebrehawaryat; Nigir, Bogale; Tilahun, Mulugeta; Terefe, Hailu (2022)
Building capacity of key implementing stakeholders is a prerequisite for successful implementation of projects. We have caried capacity building training on several topics under the framework of Sustainable Intensification of Mixed Farming Systems (SI-MFS) initiative. Briefing on SI-MFs, crowdsourcing platform for accelerated varietal evaluation and selection, and potential of local landraces for breeding and yield improvement for sustainable development were given for a total of 39 participants from 9 district agricultural officers, 18 kebele level extension workers and 12 selected model farmers from norther, central and southern parts of the country. This training workshop has also provided opportunity to strengthen collaboration among different actors of the project within the same district as well as across country. Furthermore, participants from the different corners of the country have shared experience and gained common understanding of the initiative to be implemented in their respective areas.